Dark waters [videorecording (DVD)] - Ruffalo, Mark; Hathaway, Anne, 1982-; Robbins, Tim, 1958-; Camp, Bill (Universal, 2020)
Inspired by a shocking true story, a tenacious attorney uncovers a dark secret that connects a growing number of unexplained deaths due to one of the world's largest corporations. In the process, he risks everything, his future, his family, and his own life to expose the truth.